2019
DOI: 10.1088/1742-6596/1378/4/042003
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and business activities: a case of cassava farmers in Ogun state, Nigeria.

Abstract: Climate change is an observable variation in the climate systems that are attributable to human (anthropogenic) activities and natural process (biogeographical), which alters the atmospheric composition of the earth and ultimately leads to global warming. The relationship between climate change (measured by increasing temperature trend and decreasing rainfall trend) and the business activities of cassava farmers in Ogun State, Nigeria appears not to have been fully examined; this study examines the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Once more, 97.4% of the producers used fertilizers in the right amounts. It should be emphasized that increasing cassava yield in this period of climate change has been successfully accomplished by applying both organic and inorganic fertilizers (Paul et al, 2019). Again, 97.4% of the cassava farmers adopted efficient and effective use of insecticides.…”
Section: Cassava Farmers' Adaptation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once more, 97.4% of the producers used fertilizers in the right amounts. It should be emphasized that increasing cassava yield in this period of climate change has been successfully accomplished by applying both organic and inorganic fertilizers (Paul et al, 2019). Again, 97.4% of the cassava farmers adopted efficient and effective use of insecticides.…”
Section: Cassava Farmers' Adaptation Strategiesmentioning
confidence: 99%
“…Less rainfall shrivels cassava tubers that are growing in the soil, causing deterioration and a decrease in size and market value. Rainfall increases spawn a variety of pests and diseases that heavily consume cassava leaves, lowering the photosynthetic activity of cassava plants (Paul et al, 2019). It is reported that Nigeria's cassava crop would continue to decrease as long as climate change persists (Anarah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%